The Sutton Hoo ship burial - University of Toronto. Centre for Medieval Studies (Toronto : University of Toronto Press, 1972)
Tells of the discovery and excavation of the ship on Sutton Hoo in Suffolk, England. This ship is believed to be a memorial to an Anglo-Saxon king who died around 650 A.D.
Keywords: Anglo-Saxons.; Sutton Hoo Ship Burial (England); Suffolk (England) -- Antiquities; England -- Antiquities